Comparación de los factores familiares de adolescentes consumidores y no consumidores del municipio Barrancas La Guajira (2022)
As occurs in almost all countries in the region, drug use has been increasing in recent years. As in most nations of the world, the age of initiation of drug use has been decreasing slightly. That is why the objective of this study was to compare the family factors of adolescent SPA consumers and non-consumers in Barrancas la Guajira, for this, a method was used whose approach was quantitative, since it sought to measure objectively family factors related to the consumption of psychoactive substances